1998
DOI: 10.1083/jcb.140.2.409
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Signaling Is Required for Maintenance of Differentiated Phenotype, Control of Proliferation, and Hypertrophy in Chondrocytes

Abstract: To examine the role of bone morphogenetic protein (BMP) signaling in chondrocytes during endochondral ossification, the dominant negative (DN) forms of BMP receptors were introduced into immature and mature chondrocytes isolated from lower and upper portions of chick embryo sternum, respectively. We found that control sternal chondrocyte populations expressed type IA, IB, and II BMP receptors as well as BMP-4 and -7. Expression of a DN-type II BMP receptor (termed DN-BMPR-II) in immature lower sternal (LS) cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(107 citation statements)
references
References 47 publications
4
101
1
1
Order By: Relevance
“…Bmp-2 levels are found in both human and murine OA cartilage where they help to promote chondrocyte differentiation and hypertrophy in comparison to areas of least OA involvement 41 . In contrast, TGF-beta levels are observed initially to increase during the onset of OA, and then decrease during later stages, based on expression studies in human osteoarthritic cartilage samples 24 .…”
Section: Developmental Signaling Pathways In the Pathophysiology Of Oamentioning
confidence: 99%
“…Bmp-2 levels are found in both human and murine OA cartilage where they help to promote chondrocyte differentiation and hypertrophy in comparison to areas of least OA involvement 41 . In contrast, TGF-beta levels are observed initially to increase during the onset of OA, and then decrease during later stages, based on expression studies in human osteoarthritic cartilage samples 24 .…”
Section: Developmental Signaling Pathways In the Pathophysiology Of Oamentioning
confidence: 99%
“…In contrast, expression of Bmpr1b is restricted in early mesenchymal cells and differentiated chondrocytes (Ashique et al, 2002). Over-expression of a dominant-negative Bmpr1b but not Bmpr1a inhibits chondrocyte differentiation (Enomoto-Iwamoto et al, 1998) and overexpression of a constitutively active Alk-2 promotes chondrocyte maturation (Zhang et al, 2003a) in chicken sternal chondrocytes. Over-expression of a dominant-negative Bmpr1b also inhibits osteoblast differentiation in osteoblast precursor cells .…”
Section: Biological Functions Of Bmpsmentioning
confidence: 99%
“…[22] Chondrocyte culture Chondrocytes were isolated from E17 chick embryos by enzymatic digestion of upper and lower sternal explants with 0.15% collagenase and 0.25% trypsin for 3 hours at 37°C as previously reported. [23] Chondrocytes were kept in DMEM/10% FBS except where indicated.…”
Section: Reagentsmentioning
confidence: 99%
“…We had previously shown that LS chondrocytes remain immature for more than two weeks in culture, while US chondrocytes expressed a mature phenotype, marked by high levels of alkaline phosphatase activity and collagen type X expression from the beginning of culture. [23] Whole cell lysates were prepared from both LS and US culture and the endogenous, steady-state expression levels of RhoA, Rac-1, and Cdc42 proteins were examined by immunoblot analysis (Fig. 1A, Total).…”
Section: Rho Gtpase Activities In Immature and Mature Chondrocytesmentioning
confidence: 99%